2009
DOI: 10.1167/iovs.09-3418
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Genetic and Clinical Findings in Spanish Patients with X-linked Juvenile Retinoschisis

Abstract: The prevalent p.Gln154Arg mutation is first reported in this work and presents a common origin in Spanish patients with XLRS. In addition, de novo mutations mainly occur in CG dinucleotides. Despite the large mutational spectrum and variable phenotypes, no genotype-phenotype correlations were found. Identifying the causative mutation is helpful in confirming diagnosis and counseling, but cannot provide a prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…Given the high number of RS1 mutations, several studies investigated a possible correlation between genotype and phenotype. Even though some reports describe a correlation between specific variations and the severity of clinical phenotype (22,23), the majority of published studies found that XLRS patients had relatively uniform clinical manifestations, although with great intra-familial variation in age at onset and progression (1,(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…Given the high number of RS1 mutations, several studies investigated a possible correlation between genotype and phenotype. Even though some reports describe a correlation between specific variations and the severity of clinical phenotype (22,23), the majority of published studies found that XLRS patients had relatively uniform clinical manifestations, although with great intra-familial variation in age at onset and progression (1,(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies reporting clinical features of XLRS in a series of families have been reported world-wide (Apushkin et al, 2005b; Atchaneeyasakul et al, 2010; Eksandh et al, 2000; Forsius et al, 1963; George et al, 1995, 1996; Hewitt et al, 2005; Kellner et al, 1990; Lesch et al, 2008; Pimenides et al, 2005; Renner et al, 2008; Riveiro-Alvarez et al, 2009; Shinoda et al, 2000; Shukla et al, 2007; Simonelli et al, 2003; Vainio-Mattila et al, 1969; Xu et al, 2011). The penetrance of XLRS is almost complete but clinical expression is highly variable (Sieving, 1998).…”
Section: Clinical Findings Of Congenital Xlrsmentioning
confidence: 99%
“…The RS1 RNA transcript contains 3040 nucleotides [15], and the RS1 protein, expressed in photoreceptor and bipolar cells as a homo‐oligomeric protein complex, is involved in maintaining retinal integrity [16,17]. Although over 190 unique variants in the RS1 gene have been reported and studied in XLRS patients, the severity of visual impairment of XLRS does not correlate strongly with mutation type [18–24].…”
Section: Introductionmentioning
confidence: 99%